Merekonstruksi Paradigma Politik Pemuda GMIM Dalam Bingkai Teologi Politik - Prayer Waraney Lorend Mamangkey; Hendry C M Runtuwene (PT. Giat Konseling Nusantara, 2026)
This study explores the relationship and implementation of political theology in shaping the transformative participation of GMIM (Minahasa Evangelical Christian Church) youth in Manado, North Sulawesi. Political theology, as a discipline that studies the intersection between Christian faith and the public sphere, offers a critical framework for understanding how theological beliefs influence views and actions toward justice, power, and community governance. The main focus of this study is to examine how GMIM youth, as vital agents in the context of the Minahasa church and society, can internalize the principles of political theology. We will analyze how concepts such as divine justice, the prophetic calling of the church, and Christian social responsibility can encourage them to engage actively and constructively in responding to crucial GMIM issues.